1993
DOI: 10.1007/bf00982302
|View full text |Cite
|
Sign up to set email alerts
|

Chemical ecology of the palm weevilRhynchophorus palmarum (L.) (Coleoptera: Curculionidae): Attraction to host plants and to a male-produced aggregation pheromone

Abstract: Attraction to host plants by adultRhynchophorus palmarum (L.) palm weevils was studied in the field and in the laboratory. Chemical analysis revealed the presence of ethanol and ethyl-acetate in stems of coco palms and in pineapple fruits and of pentane, hexanal, and isopentanol in coco stems. In the olfactometer, the first two compounds and isoamyl-acetate were attractive to the insects and the last three compounds, although not attractive by themselves, increased attractiveness when mixed with the first two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0
16

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 9 publications
2
58
0
16
Order By: Relevance
“…Host plant volatiles alone (e.g. Hughes, 1973b;Jaffe et al, 1993) or hormonal changes triggered by midgut expansion (Hughes & Renwick, 1977) can stimulate male pheromone release, or perhaps pheromone composition may be altered by feeding as it can be by beetle density (Pierce et al, 1989). These relationships remain to be clarified for A. vittatum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Host plant volatiles alone (e.g. Hughes, 1973b;Jaffe et al, 1993) or hormonal changes triggered by midgut expansion (Hughes & Renwick, 1977) can stimulate male pheromone release, or perhaps pheromone composition may be altered by feeding as it can be by beetle density (Pierce et al, 1989). These relationships remain to be clarified for A. vittatum.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous examples of host plant volatiles that are potent synergists to male pheromone signals (e.g. Wood, 1982;Dickens, 1989;Bartelt et al, 1990;Dickens et al, 1990;Jaffe et al, 1993;Raffa et al, 1993, and references therein;Bartelt, 1999). Although evidently not essential for A. vittatum signalling (as males feeding on pollen did attract), synergy with host volatiles could account for increased attraction with the rate of cucurbit feeding.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that the aggregation pheromone [(E)-6-methyl-2-hepten-4-ol, rhynchophorol] only attracts males when either the complete bouquet of plant volatiles or ethyl acetate alone is present. 109 Metamasius hemipterus is a serious sugarcane pest distributed throughout Central and South America, the West Indies, Mexico and Florida (U.S.). The attraction of adult beetles toward host plant parts in an olfactometer was reported, 110 as well as captures in field traps baited with different mixtures of plant parts and the aggregation pheromone, an 8:1 mixture of 4-methyl-5-nonanol and 2-methyl-4-heptanol.…”
Section: Other Selected Topicsmentioning
confidence: 99%
“…Originado no sudeste da Ásia foi introduzida no Brasil através do estado da Bahia (MIRISOLA FILHO, 2002), sendo esse, segundo o IBGE (2009), o maior produtor brasileiro com 79.596 ha, produção de 467.080 toneladas e produtividade de 5.868 kg/ha.…”
Section: Introductionunclassified